DISCOVERY LEARNING DISERTAI PERTANYAAN DIVERGEN UNTUK MENINGKATKAN KETERAMPILAN ARGUMENTASI SISWA PADA PEMBELAJARAN BIOLOGI - Azizah Nur Halimah; harlita harlita; Sri Dwiastuti (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
IMPLEMENTATION OF DISCOVERY LEARNING MODELS WITH DIVERGENT QUESTIONS TO IMPROVE STUDENTS’ ARGUMENTATION SKILLS ON THE BODY DEFENSE SYSTEM MATERIALAbstractThis study aims to apply the discovery learning model with divergent questions to improve students' argumentation skills on the material of the body's defense system. The subjects of the study were students of class XI MIA 3 Gondangrejo Public High School consisting of 36 students. This research is a Classroom Action Research (CAR). Data collection techniques were carried out through oral argumentation observation sheets, written argumentation evaluation question sheets, interviews, and documentation. A validity test was done by the triangulation method. Data analysis techniques were using interactive model analysis, namely data reduction, data presentation, and drawing conclusions. The research procedure is a continuous spiral model. The results of the application of discovery learning models accompanied by divergent questions show that oral argumentation skills in Cycle I are 26.67% reaching level 1 and 73.33% reaching level 3, increasing to Cycle II ie 16.67% reaching level 1, 8.33% reaching level 2, 62.50% reaching level 3 and 12.50% reaching level 4. Students' written argumentation skills in Cycle I was 16.6% reaching level 1, 22.7% reaching level 2, and 60.5% reaching level 3, increased to Cycle II, namely 7.78% reaching level 1, 6.67% reaching level 2 and 85.56% reaching level 3. Based on the results of the study, it was concluded that through the application of discovery learning models accompanied by divergent questions can improve argumentation skills students on body defense system material. AbstrakPenelitian ini bertujuan untuk menerapkan model discovery learning disertai pertanyaan divergen untuk meningkatkan keterampilan argumentasi siswa pada materi sistem pertahanan tubuh. Subjek penelitian adalah siswa kelas XI MIA 3 SMA Negeri Gondangrejo yang terdiri dari 36 siswa. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK). Teknik pengumpulan data dilakukan melalui lembar observasi argumentasi lisan, lembar soal evaluasi argumentasi tertulis, wawancara, dan dokumentasi. Uji validitas dilakukan dengan metode triangulasi. Teknik analisis data menggunakan analisis model interaktif yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Prosedur penelitian adalah model spiral yang saling berkesinambungan. Hasil penerapan model discovery learning disertai pertanyaan divergen menunjukkan keterampilan argumentasi lisan pada Siklus I yaitu 26,67% tergolong level 1 dan 73,33% tergolong level 3, mengalami peningkatan pada Siklus II yaitu 16,67% tergolong level 1, 8,33% tergolong level 2, 62,50% tergolong level 3 dan 12,50% tergolong level 4. Keterampilan argumentasi tertulis siswa pada Siklus I yaitu 16,6% tergolong level 1, 22,7% tergolong level 2, dan 60,5% tergolong level 3, mengalami peningkatan pada Siklus II yaitu 7,78% tergolong level 1, 6,67% tergolong level 2 dan 85,56% tergolong level 3. Berdasarkan hasil penelitian disimpulkan bahwa melalui penerapan model discovery learning disertai pertanyaan divergen dapat meningkatkan keterampilan argumentasi siswa pada materi sistem pertahanan tubuh.